The Future of Educational Leadership in Light of the Crisis Management Aspects - Al-Widyan, Sharie Ayed (Journal of Risk and Crisis Management, 2021)
The current descriptive survey study aims to address the problem of the apparent inadequacy of most school leaders in managing crises and disasters and to anticipate future scenarios for such crises. To achieve this, the researcher designed a questionnaire consisting of thirty-one (31) items distributed on three axes: The reality of school leadership, potential crises, and the anticipated future of the leadership in light of crisis management. was validated by calculating the correlated parameters statistically, and its stability by (test-retest) method on an external sample and then the Pearson correlation coefficient between their estimates in both times, and the questionnaires was distributed to the study’s sample consisting of one hundred eighty (180) general education leaders in Wadi Al-Dawasir. The study’s population is two hundred forty-six (246) male and female leaders, agents, and assistants. The study revealed that the leaders’ abilities in crisis management in the current reality and in anticipating the potential crises were weak while the expected scenario for the future of school leadership in light of crisis management was strongly positive. With a statistically significant difference at the level of (α = 0.05) due to the gender variable in favor of female leaders in the “Potential crises” axis, and statistically significant differences due to the variable of experience in leadership in all axes in favor of “Five years or more”. The researcher recommends that the Education Department should ensure that school leaders possess the skills of crisis management, the need to adopt one of the contemporary models in crisis management, and the need to establish an active unit for crisis management in schools.